Liaison Officer and Business Consultant on Tenants Siomay Pa'dee and Cahaya Kebab & Burger - Jihardianti Jihardianti (CV. ALIM'SPUBLISHING, 2026)
The Polbeng Business Exhibition is an event organized by students of the International Business Administration Study Program at the Bengkalis State Polytechnic as a form of applying the business theories learned during lectures. This event serves as a platform for promotion, entrepreneurship training, and a means of introducing MSME products to the community. This project focuses on Siomay Pa'dee and Cahaya Kebab & Burger, two participants in the Polbeng Business Expo Chapter II. The objective of this project is to analyze the preparation process, implementation, and results achieved by both MSMEs during the exhibition, particularly in terms of promotion, business management, and digital marketing. The methods used include observation and documentation. Additionally, the role of the liaison officer is crucial in bridging communication and coordination between organizers, MSME participants, and other stakeholders, while the business consultant provides recommendations for business development from preparation to evaluation during the expo. The project results show that the tenants' participation in the expo successfully increased product promotion through the creation of profile videos, promotional videos, product catalog, and digital marketing strategies on various social media platforms. In addition, financial reports and activity logs are important tools in evaluating the performance of MSMEs. This expo proved to be beneficial for students as practical experience in event and business management, as well as for MSMEs as a means to expand their market reach and enhance their business image.